Identification and functional characterization of a novel surfactant protein A2 mutation (p.N207Y) in a Chinese family with idiopathic pulmonary fibrosis. Issue 9 (30th June 2020) - Liu, Lv; Qin, Jieli; Guo, Ting; Chen, Ping; Ouyang, Ruoyun; Peng, Hong; Luo, Hong
Abstract: Background: Idiopathic pulmonary fibrosis (IPF) is a serious disorder with a high mortality rate worldwide. It is characterized by irreversible scarring of the lung parenchyma resulting from excessive collagen production by proliferating fibroblasts/myofibroblasts. Previous studies have revealed that mutations in surfactant protein‐related genes and telomerase complex genes are crucial underlying genetic factors. Methods: In this study, we enrolled a family with IPF from the central southern region of China. Whole‐exome sequencing was employed to explore candidate genes in this family. Real‐time PCR and western blotting were used to study the functions of the identified mutations in vitro. Results: A novel mutation (NM_001098668.4: c.619A>T; NP_001092138.1: p.N207Y) in surfactant protein A2 ( SFTPA2, ), having not been previously reported to be a mutation, was identified and co‐separated with all affected individuals in the IPF family. Functional research further revealed that the novel mutation affects the secretion of SFTPA2 protein and induces endoplasmic reticulum stress as well as apoptosis in A549 cells. Conclusion: We are confident that this novel mutation (NM_001098668.4: c.619A>T; NP_001092138.1: p.N207Y) in SFTPA2 is the genetic mutation of the IPF family. Our study not only confirms the importance of SFTPA2 in IPF but also expands the spectrum of SFTPA2 mutations and contributes to the genetic diagnosis and counseling of IPF patients. Abstract : Mutation in SFTPA2 was rare reported, and we identified a novel pathogenic mutation (p.N207Y) of SFTPA2 gene in idiopathic pulmonary fibrosis (IPF) patients in this study. Functional study further confirmed the novel mutation may affect the expression and secretion of surfactant protein A2 protein and induce endoplasmic reticulum stress and apoptosis. Our study not only confirmed the importance of SFTPA2 in IPF, but also expanded the spectrum of SFTPA2 mutations and contributed to the genetic diagnosis and counseling of IPF patients.